nahkiaismertoja pyyntiin viritettyinä - Järvi, T. H.
fyysinen kuvaus: vaaka
Keywords: kalastus; koskikalastus; merrat; pyyntivälineet; Suomen entinen kunta/pitäjä, Kymi, Langinkoski, Kymi, Langinkoski, Langinkoski